AT HOME IN THE LANGUAGE OF THE SOUL exploring jungian discourse and psyche's grammar of... transformation. - Evetts-Secker, Josephine ([S.l.] : ROUTLEDGE, 2021)
Language has a primary importance in Jungian psychology and its practice. C. G. Jung saw every act of speech as a psychic event. Even the "worker" words in language, like prepositions or conjunctions, carry particular archetypal energies, working dynamically and daimonically in the conduct of transformational narrative and realizing both personal and collective purposes. This book aims to deepen our consciousness of psyche's speech as it occurs in our professional discourses, in the psychoanalytic encounter, in dreams, fairy tales, myths and poetry. Vividly exploring the grammar of psyche, we are urged to constantly kindle and rekindle our engagement with language.
OCLC-licensed vendor bibliographic record.
Keywords: Jungian psychology; Psycholinguistics; PSYCHOLOGY / Mental Health